2020
DOI: 10.1007/s10257-020-00485-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of technology fit and appropriation in business networks: evidence from blockchain implementations

Abstract: Existing information systems research thoroughly explains how task-technology fit and appropriation affect performance on an individual or group level. This was appropriate for many years, as technology is typically used to fulfill a certain task on these levels. Today, however, companies are tightly interconnected and rely on business networks to develop, produce, and deliver products and services. They collaboratively engage in joint implementation and utilization of new technologies that are applied and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…The primary purpose of the model by Goodhue and Thompson (1995) has been at the individual level. Seebacher et al (2020) put forward the extension of this model at the group level. Various modifications have been done in this theory accordingly.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary purpose of the model by Goodhue and Thompson (1995) has been at the individual level. Seebacher et al (2020) put forward the extension of this model at the group level. Various modifications have been done in this theory accordingly.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Graphs become vicarious to understand particular scientific concepts. Seebacher et al (2020) employed the graphical multiuser environment (hereafter as MUVE) to involve pupils in science inquiry learning and investigated self-efficacy. The study found that MUVE has been appealing and surges students’ science learning.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…data transparency and immutability, smart contracts, decentralized network, digital currencies, etc) may encourage companies to launch blockchain-based projects. Nevertheless, to succeed early adopters should have a discipline and acceptance of emerging trends, like blockchain as a service [69,72] and asset tokenization [57,64]. ii.Value delivery.…”
Section: ) Business Models Innovationmentioning
confidence: 99%
“…Therefore, blockchain integration with other technologies can increase the quality of providing services. Additionally, some studies focused on how blockchain can optimize data structuring [45,54,72]. Since data is available to all actors in the network, the decentralized nature of blockchain technology increases the transparency of information.…”
Section: ) Processes Optimization and Integration With Other Technolo...mentioning
confidence: 99%
See 1 more Smart Citation